2018
DOI: 10.1007/s00264-018-3934-7
|View full text |Cite
|
Sign up to set email alerts
|

Joint hyperlaxity prevents relapses in clubfeet treated by Ponseti method—preliminary results

Abstract: Joint hyperlaxity could be a protective factor for clubfoot relapse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 25 publications
0
10
0
1
Order By: Relevance
“…Next, we assumed that more severe initial deformities underlie higher congenital deforming forces and are asso- (Avilucea et al 2009), (Dinesh et al 2017), (Chong et al 2014), (Haft et al 2007), (Limpaphayom and Sailohit 2019), (Mahan et al 2017), (Cosma et al 2018), (Mootha et al 2011), (Morcuende et al 2004), (Morcuende et al 2005), (Gelfer et al 2014), (Panjavi et al 2012), (Ramírez et al 2011), (Sangiorgio et al 2016), (Kang and Park 2015), (Sangiorgio et al 2017), (Zhao et al 2018) (Kuzma et al 2019), (Little et al 2019), (Vo and Huynh 2016) ciated with a higher recurrence risk. However, our analysis revealed inconclusive findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, we assumed that more severe initial deformities underlie higher congenital deforming forces and are asso- (Avilucea et al 2009), (Dinesh et al 2017), (Chong et al 2014), (Haft et al 2007), (Limpaphayom and Sailohit 2019), (Mahan et al 2017), (Cosma et al 2018), (Mootha et al 2011), (Morcuende et al 2004), (Morcuende et al 2005), (Gelfer et al 2014), (Panjavi et al 2012), (Ramírez et al 2011), (Sangiorgio et al 2016), (Kang and Park 2015), (Sangiorgio et al 2017), (Zhao et al 2018) (Kuzma et al 2019), (Little et al 2019), (Vo and Huynh 2016) ciated with a higher recurrence risk. However, our analysis revealed inconclusive findings.…”
Section: Discussionmentioning
confidence: 99%
“…Average compliance rate was 89% in those studies that did not report associations, ranging from 70% to 100% in the recurrent group, whereas average compliance rate was 66% in those studies reporting significant associations, ranging from 0% to 40% in the recurrent group. (Chong et al 2014) (Dinesh et al 2017), (Gelfer et al 2014), (Haft et al 2007), (Hallaj-Moghaddam et al 2015), (Kuzma et al 2019), (Little et al 2019), (Morcuende et al 2004), (Morcuende et al 2005), (Shabtai et al 2015), (Zhao et al 2018) Initial age at start of treatment (Willis et al 2009) (Chong et al 2014), (Gelfer et al 2014), (Haft et al 2007), (Hallaj-Moghaddam et al 2015), (Kang and Park 2015), (Kuzma et al 2019), (Limpaphayom and Sailohit 2019), (Little et al 2019), (Liu et al 2018), (Ramírez et al 2011), (Mootha et al 2011), (Morcuende et al 2004), (Morcuende et al 2005) (Cosma et al 2018), (Mootha et al 2011), (Morcuende et al 2005), (Morcuende et al 2004), (Ramírez et al 2011), (Willis et al 2009) Surgeon vs. physiotherapist directed treatment (Janicki et al 2009) Tenotomy (Chong et al 2014), (Cosma et al 2018), (Dinesh et al 2017), (Hallaj-Moghaddam et al 2015, (Kuzma et al 2019), (Little et al 2019), (Panjavi et al 2012)…”
Section: Behavioral Factorsmentioning
confidence: 99%
“…Ponseti suggested that clubfeet in children having "loose ligaments" were less prone to relapses (24). Recently, Cosma et al (46) suggested that joint hyperlaxity could be a protective factor for relapse; a finding they considered preliminary given the small number of patients in their study. We sought to determine if generalized joint hypermobility, influenced the Ponseti treatment of clubfoot in a cohort of 57 patients with clubfoot deformity (47).…”
Section: Influence Of Generalized Joint Hypermobility On Clubfoot Treatmentmentioning
confidence: 94%
“…As joint hyperlaxity can be a protective factor against relapse in clubfeet and we considered that it might influence the stiffness of tendons on elastograms, we also decided to exclude patients who exhibited any sign of hyperlaxity from the study. 12 Further, we opted to exclude patients who had report any type of foot or ankle pain in the three months prior to the evaluation as this could have been correlated with tendinopathy, which might influence stiffness measurements. None of the patients included in this study practised performance sports, which can also influence results as athletes can have stiffer tendons than the general population.…”
Section: Methodsmentioning
confidence: 99%